The importance of GRACE score in health care planning of patients after acute myocardial infarction - Đorđević Marina; Davidović Jelica; Resimić Radmila; Otašević Dijana; Marković-Nikolić Nataša; Davidović Aleksandar (Association of Nurses Technicians and Midwives, 2021)
Introduction: Acute myocardial infarction (AIM) is ischemic myocardial necrosis and is associated with a number of adverse outcomes that complicate patient health care. Assessment of patient status, risk factors, and adverse outcomes has a significant impact on patient care planning after AIM. The GRACE (Global Registry of Acute Coronary Events) score is of great importance in risk stratification in these patients. Objective: To determine the importance of determining the GRACE score in order to set priorities in the planning of patient care after acute myocardial infarction. Method: A retrospective study examined 50 patients, both sexes, aged 28 to 75 years, with a diagnosis of acute myocardial infarction, undergoing percutaneous coronary intervention (PKI), who were treated at the Zvezdara Clinical Hospital in Belgrade during the research period, from January to March 2020. Data were taken from the medical records of these patients. During the study, AIM type, comorbidities, CVD risk factors, GRACE score and frequency of complex nursing interventions in patients with low, moderate, and high-risk of adverse cardiac events were monitored. Results: Out of a total of 50 examinees with AIM treated with PKI, 74% had STEMI and 26% NSTEMI. 84% of patients had positive family history, 64% hypertension, 2% diabetes, 48% obesity, 52% were smokers and 6% of them were using alcohol. The values of the GRACE score were increased as follows: in four patients more than 140, while in one of them a moderate value was recorded, and in one low value of the GRACE score. In the course of six months, three patients, who had high GRACE scores on hospitalization, had a lethal outcome. Complex nursing interventions in the intensive care unit are more common in patients who have high GRACE score values after AIM. Conclusion: The GRACE score can be used as an important guideline in planning the health care of patients after an acute myocardial infarction.